Case Report: Survival of A Coronavirus Disease-2019 (Covid-19) Patient with Acute Respiratory Distress Syndrome (ARDS) in Dr. Soetomo Hospital, Surabaya, Indonesia - Soedarsono, Soedarsono; Semedi, Bambang Pudjo; Setiawati, Rosy; Meliana, Resti Yudhawati; Kusmiati, Tutik; Permatasari, Ariani; Bakhtiar, Arief; Syafa'ah, Irmi; Indrawanto, Dwi Wahyu (Folia Medica Indonesiana, 2020)
An outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that began in Wuhan, China has spread rapidly in multiple countries of the world and has become a pandemic. Currently, there is no vaccine or specific antiviral for COVID-19. A study reported 7.3% of critical patients admitted to ICU, 71% of them required mechanical ventilation, and 38.5% of them were survived. Herein, we reported a 54 year old man with Acute Respiratory Distress Syndrome (ARDS) of COVID-19 who survived the disease. Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) assay of nasopharyngeal and oropharingeal swabs were positive for SARS-CoV-2. Diagnosis of ARDS was also according to clinical symptoms, laboratory, chest radiograph, and chest CT scan. Alcaligenes faecalis and Candida albicans were also identified from sputum culture. Treatment for this patient was causal and supportive therapy, including antibiotic, antiviral, and antifungal therapy according to the culture results, fluid resuscitation, and oxygen supply from the mechanical ventilator. This patient was survived and discharged on hospital day-29. A fibrosis in parenchyma pulmonary and sensory peripheral neuropathy occurred after survived from ARDS. Monitoring of clinical, laboratory, and chest radiograph were continued after the patient discharged from the hospital. This case highlights the importance of early diagnosis and effective treatment to the care of COVID-19 patient.